Improving the Education of Children's Learning Process in Kedungasri Village, Ringinarum Sub-District - Ismi Alvia Damayanti; Purnama Cahya Pertiwi; Nabila Adinda Larasati; Flony Syera Lestari; Retno Mukti; Lutfiyah Lutfiyah (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
One of the responsibilities that a student has is to contribute to society. This responsibility can be realized through the Community Service Program (KKN). KKN is an activity program carried out in applying the knowledge and theories that have been obtained during lectures and then practiced directly to the community. Education is an effort that can accelerate the development of human potential to be able to carry out the tasks assigned. One of the contributions that KKN students can make to the community in the field of education can be realized by striving to improve the teaching and learning process of children in Kedungasri Village, Ringinarum District, Kendal Regency. This research aims to improve the teaching and learning process of children in Kedungasri Village, Ringinarum District. This research method uses a qualitative approach with data collection techniques through observation, interviews, and FGDs to identify the main problems and methods used by teachers in the education process. The results of the study explained that the work program focused on developing education in Kedungasri Village by KKN students in formal, non-formal, and informal education was successfully implemented as intended. This is indicated by the achievement of the work program for the development of formal education at the kindergarten, elementary, and MI levels, the development of non-formal education at TPQ and MDA, and the development of informal learning activities by holding tutoring (bimbel)